HUBUNGAN STATUS GIZI (TB/U) TERHADAP PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA 1-3 TAHUN DI WILAYAH KERJA PUSKESMAS KORPRI KABUPATEN KUBU RAYA - Suwandi Suwandi; Ayu Rafiony (Poltekkes Kemenkes Pontianak, 2018)
Motor development is a development that controls body movements by involving coordination between the nervous system, central nerve and muscle. Activities related to gross motor development involve a mechanism that requires adequate energy and physical, so that nutritional status is one of the factors that influence gross motor development. TB / U is the most widely used index to determine nutritional status which is measured anthropometically related to gross motor development. This study aims to determine the relationship between nutritional status (TB / U) and gross motoric development of children. Observational type with cross sectional approach design The number of samples in this study were 92 children taken by random sampling. Nutritional status data were obtained by anthropometric measurements (TB / U) and categorized based on WHO Anthro 2005. Gross motor development data obtained using DDST were then categorized based on DDST assessment. In this study 40.2% short samples and 59% normal samples were found, 26.1% of samples had late gross motor development and 73.9% of samples were not late. The results of statistical tests showed a significant relationship between TB / U and gross motor development (p> 0.05). It is best to do therapy for children who experience gross motor development late to get developmental stimulation.